1995
DOI: 10.1111/j.1574-6968.1995.tb07793.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of concentration of compounds containing iron on the growth ofPorphyromonas gingivalis

Abstract: We examined the effect of the concentration of various types of iron molecules on the regulation of growth of Porphyromonas gingivalis. Bacterial growth was monitored spectrophotometrically. The hemin-depleted cells of P. gingivalis 381 were incubated in the basal medium plus test substrates such as hemoglobin, hemin, transferrin and various inorganic iron compounds. The relationship between the specific growth rate of organisms and the concentration of iron-containing compounds was determined. The value of Ks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…However, P. gingivalis does not produce siderophores or ferric reductases. Although P. gingivalis employs the Feo system to uptake ferrous iron in anaerobic or microaerophilic environments (40), growth studies have shown that P. gingivalis preferentially acquires iron in the form of heme rather than from other sources (9,41). For P. gingivalis, heme is also an essential nutrient source of protoporphyrin IX because the organism lacks the capacity to synthesize the porphyrin macrocycle de novo (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, P. gingivalis does not produce siderophores or ferric reductases. Although P. gingivalis employs the Feo system to uptake ferrous iron in anaerobic or microaerophilic environments (40), growth studies have shown that P. gingivalis preferentially acquires iron in the form of heme rather than from other sources (9,41). For P. gingivalis, heme is also an essential nutrient source of protoporphyrin IX because the organism lacks the capacity to synthesize the porphyrin macrocycle de novo (2).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other hemoproteins, hemoglobin is utilized more efficiently by P. gingivalis under heme-limiting conditions (41). The concentration of heme in healthy gingival fluid is low (57), and the ability to scavenge heme from limited hemoproteins, particularly hemoglobin, appears to be critical for the colonization of this organism in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of hemin and hemoglobin to support 50% of the maximal growth rates are 1-5 M and 1.7 nM, respectively (37), which implies that the iron uptake/utilization systems from hemin and hemoglobin may have, at least in part, different pathways. In a previous study (11), we presented a hypothetical mechanism of the iron uptake/utilization from erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of Haptoglobin on the Binding of Hemoglobin to HbRHaptoglobin has the ability to bind hemoglobin (36) and suppress the growth of P. gingivalis in a medium containing hemoglobin (37). To determine whether this growth suppression by haptoglobin is involved in the interaction of hemoglobin with HbR, the effect of haptoglobin on the binding of hemoglobin to HbR was examined.…”
Section: Growth Retardation and Hbr Release By Lactoferricinmentioning
confidence: 99%
“…The growth and virulence of P. gingivalis has been reported to be dependent on the availability of iron complexes such as heme (7)(8)(9). Growth studies have indicated that P. gingivalis preferentially acquires iron in the form of hemoglobin-derived heme, a molecule comprised of a protoporphyrin IX ring with a co-ordinated central ferrous atom (10). Unlike most bacteria P. gingivalis cannot synthesize protoporphyrin IX de novo (11,12) and must also acquire this from the environment, which may explain the preferential utilization of heme by this bacterium.…”
mentioning
confidence: 99%